Low power transient analysis of PWR reload core with fixed neutron source via 3-D nodal diffusion code RAST-K. (January 2021) - Jo, YuGwon; Shin, Ho Cheol
Abstract: The rod ejection accident (REA) is the most severe reactivity-initiated accident of the pressurized water reactors (PWRs). The three-dimensional (3-D) neutron kinetics method is widely applied to the REA analysis, where the fixed neutron source is usually ignored at the hot zero power (HZP) condition. This paper describes a new capability of the 3-D nodal diffusion code, RAST-K to consider the fixed source in the low power transient analysis of the PWR reload core. The RAST-K calculates the fixed source originated from the spontaneous fission and the ( α, n) reaction, which is verified by the ORIGEN code. The new capability is applied to the REA analysis at the HZP condition for various initial core power levels and the results are compared with those of ignoring the fixed source. The numerical results show that the fixed source significantly suppresses the power pulse of the REA by imposing the initial negative reactivity.